Analysis of barriers to the development of Industrial Internet of Things technology and ways to overcome them. Issue 1 (January 2021) - Zhmud, V; Liapidevskiy, A; Avrmachuk, V; Sayapin, V; Stukach, O; Roth, H
Abstract: As is known, in 2019 the national program "Digital Economy of the Russian Federation" was launched. In the first phase, nine roadmaps were developed, of which six were approved by the Prime Minister. Participation in the development of these roadmaps provides a fresh perspective on some particular problems. The authors reveal some details of the approach to the implementation of the "Industrial Internet of Things" direction. Some specific differences of the industrial Internet from the regular Internet are discussed using examples. Some conclusions are drawn about the directions for further research in this area.